Japanese democracy : power, coordination, and performance - Richardson, Bradley M. (Yale University Press, 1997)
In this new analysis of democracy in Japan, Bradley Richardson refutes the widely accepted hypothesis that postwar Japan has been a semiauthoritarian and consensual state, heavily influenced by corporations and led by the government bureaucracy. On the contrary, Richardson's extensive newspaper and documentary research shows that Japanese political life has been extremely fragmented and discordant at all levels - in the bureaucracy, legislatures, parties, and interest groups and in business and industry.